Iterative Learning Control An Optimization Paradigm - Owens, David H.; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2016)
This book develops a coherent theoretical approach to algorithm design for iterative learning control based on the use of optimization concepts. Concentrating initially on linear, discrete-time systems, the author gives the reader access to theories based on either signal or parameter optimization. Although the two approaches are shown to be related in a formal mathematical sense, the text presents them separately because their relevant algorithm design issues are distinct and give rise to different performance capabilities. Together with algorithm design, the text demonstrates that there are new algorithms that are capable of incorporating input and output constraints, enable the algorithm to reconfigure systematically in order to meet the requirements of different reference signals and also to support new algorithms for local convergence of nonlinear iterative control. Simulation and application studies are used to illustrate algorithm properties and performance in systems like gantry robots and other electromechanical and/or mechanical systems. Iterative Learning Control will interest academics and graduate students working in control who will find it a useful reference to the current status of a powerful and increasingly popular method of control. The depth of background theory and links to practical systems will be of use to engineers responsible for precision repetitive processes. Advances in Industrial Control aims to report and encourage the transfer of technology in control engineering. The rapid development of control technology has an impact on all areas of the control discipline. The series offers an opportunity for researchers to present an extended exposition of new work in all aspects of industrial control.
Iterative Learning Control: Background and Review. Mathematical and Linear Modelling Methodologies -- Norm Optimal Iterative Learning Control: An Optimal Control Perspective -- Predicting the Effects of Non-minimum-phase Zeros -- Predictive Norm Optimal Iterative Learning Control -- Other Applications of Norm Optimal Iterative Learning Control -- Successive Projection Algorithms -- Parameter Optimal Iterative Learning Control -- Robustness of Parameter Optimal Iterative Learning Control -- Multi-parameter Optimal Iterative Learning Control -- No Normal 0 false false false EN-GB X-NONE X-NONE/* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-fareast-language:EN-US;} nlinear Iterative Learning Control and Optimization.
Keywords: Control engineering; System theory; Control theory; Artificial intelligence; Machinery; Robotics; Automation; Control and Systems Theory; Systems Theory, Control; Artificial Intelligence; Machinery and Machine Elements; Control, Robotics, Automation